Seismic analysis of a 30 story salemba apartment in Jakarta subjected to nabire earthquake excitation - Suhatril, Meldy (2006)
The earthquake loading as a lateral loading should be taken into account in the analysis of a highrise building, especially for places in high seismic zones. The acceleration of ground motion of the Nabire earthquake in Indonesia will be analyzed and the response spectrum will be constructed by using DADISP software. There are three components of Nabire earthquake record that was recorded using an accelerograph, which are the horizontal component north south direction (BHN), east west direction (BHE) and the vertical direction (BHZ). The horizontal component north- south direction with peak ground acceleration (PGA) of about 400 cm/s2 will be used to construct the response spectrum. The static equivalent lateral forces analysis based on the Indonesia seismic code procedure will be used to estimate the seismic loading. The constructed Nabire response spectrum will be applied in the analysis. The earthquake loading produced will be applied to the actual building in Jakarta (30 storey Salemba apartment) which use shear wall as structural element to resist earthquake motion. A single cantilever critical shear wall will be analyzed and designed by using structural computation software (STAADPRO).